2017
DOI: 10.3892/ol.2017.6638
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhiza extract inhibits TPA-induced MMP-9 expression and invasion through the MAPK/AP-1 signaling pathway in human breast cancer MCF-7 cells

Abstract: Cancer cell invasion is crucial for metastasis. A major factor in the capacity of cancer cell invasion is the activation of matrix metalloproteinase-9 (MMP-9), which degrades the extracellular matrix. Salvia miltiorrhiza has been used as a promotion for blood circulation to remove blood stasis. Numerous previous studies have demonstrated that S. miltiorrhiza extracts (SME) decrease lipid levels and inhibit inflammation. However, the mechanism behind the effect of SME on breast cancer invasion has not been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Additionally, it has been indicated that MAPK families, including JNK, ERK, and P38 kinase are also involved in cell invasion and cancer metastasis [ 45 ]. MAPK families have an important role in the activation of AP-1 through c-Jun or c-Fos phosphorylation [ 46 ]. Therefore, in the present study, we investigated the effects of casticin on PI3K/Akt and MAPK signaling pathways in the MDA-MB-231 and 4T1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been indicated that MAPK families, including JNK, ERK, and P38 kinase are also involved in cell invasion and cancer metastasis [ 45 ]. MAPK families have an important role in the activation of AP-1 through c-Jun or c-Fos phosphorylation [ 46 ]. Therefore, in the present study, we investigated the effects of casticin on PI3K/Akt and MAPK signaling pathways in the MDA-MB-231 and 4T1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, PKCδ levels were not inhibited by mLU8C‐PU. Moreover, to check whether mLU8C‐PU could inhibit the MAPKs and Akt signaling pathway, which is involved in breast cancer cell migration and invasion, the phosphorylation patterns of MAPKs and Akt in MCF‐7 cells were examined. MCF‐7 cells were treated with various concentrations of mLU8C‐PU followed by TPA (50 nM) for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…AP-1 family plays essential roles in cell proliferation and survival 28 , which critically involves in MAP kinases pathways in various cellular types 29 31 . Previous data revealed that the extracellular signal-regulated kinases (ERK) and the c-Jun NH2-terminal kinases (JNK), two essential members of MAP kinases, can be activated in VSMCs from the acutely induced hypertensive rats, with the up-regulated gene expression of c-Fos and c-Jun , as well as the enhanced AP-1 DNA-binding activity 32 .…”
Section: Discussionmentioning
confidence: 99%